Citywide community-based colorectal cancer screening in urban Shanghai: age and sex variations in risk mitigation from 1973 to 2020 - Wu, Mengyin; Gong, Yangming; Wu, Chunxiao; Peng, Peng; Chen, Lei; Li, Qi; Shi, Liang; Xiang, Yongmei; Dou, Jianming; Pang, Yi; Zhang, Xiaocong; Gu, Kai; et al. (Frontiers in Oncology, 2025)
AimsTo evaluate the impact of Shanghai’s community colorectal cancer (CRC) screening program on CRC epidemiology and risk reduction.Materials and methodsData from the Shanghai Cancer Registry (1973-2020) were analyzed. Launched in 2013, the program targets residents aged 50-74, offering free risk assessment (questionnaire and fecal tests). High-risk individuals are advised for colonoscopy (non-mandatory). Interrupted time-series analysis assessed age-standardized incidence and mortality trends.ResultsOver 3 million individuals were screened, with 18.7% high-risk and 27-32% undergoing colonoscopy. Screening did not significantly reduce CRC incidence but led to a mortality decline (annual percent change [APC]: 1.07% to −3.16%, P < 0.001). Females showed greater benefit, with incidence APC dropping from 1.93% to −0.28% (P < 0.001). No incidence reduction was seen in younger or older groups, with under-50s showing rising incidence. However, elderly mortality decreased significantly (APC: 1.47% to −3.03%, P < 0.001).ConclusionThe program significantly reduced CRC mortality, particularly in females and the elderly, though incidence trends varied by age. Despite a significant reduction in mortality, the observed stability in overall CRC incidence is an expected finding in the initial years of a screening program. This pattern is largely due to increased detection of prevalent pre-existing cases during the first screening round, which may temporarily offset the decline in incident cases.